2020
DOI: 10.1007/s40273-020-00987-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of a Dolutegravir-Based Versus Low-Dose Efavirenz-Based Regimen for the Initial Treatment of HIV-Infected Patients in Cameroon (NAMSAL ANRS 12313 Trial)

Abstract: Objectives Evidence comparing the economic and patient values of the World Health Organization’s preferred (dolutegravir 50 mg [DTG]-based) and alternative (low-dose [400 mg] efavirenz [EFV400]-based) first-line antiretroviral regimens is limited. We compared patient-reported outcomes (PROs), costs, and the cost-utility of DTG- versus EFV400-based regimens in treatment-naive HIV-1 adults in the randomised NAMSAL ANRS 12313 trial in Yaoundé, Cameroon. Methods We used cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In NAMSAL, the SF-12 PCS and MCS increased over time in both arms, with the PCS reaching levels comparable to those reported here, whereas the MCS remained lower in NAMSAL through week 48 [2]. In NAMSAL, the baseline prevalence of at least mild depression was over 23% at enrolment but had dropped to below 10% in both arms by 48 weeks, with the latter result being comparable to the prevalence in DO-REAL at baseline and 16-week follow-up, albeit using a different screening tool [2,33].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In NAMSAL, the SF-12 PCS and MCS increased over time in both arms, with the PCS reaching levels comparable to those reported here, whereas the MCS remained lower in NAMSAL through week 48 [2]. In NAMSAL, the baseline prevalence of at least mild depression was over 23% at enrolment but had dropped to below 10% in both arms by 48 weeks, with the latter result being comparable to the prevalence in DO-REAL at baseline and 16-week follow-up, albeit using a different screening tool [2,33].…”
Section: Discussionsupporting
confidence: 69%
“…Among randomized trials comparing DTG and EFV [2][3][4][5][6][7]33], only the NAMSAL trial (conducted in Cameroon) comparing DTG and low-dose EFV provided information on mental and self-reported physical health scores. Similar to this study, NAMSAL reported no difference in the prevalence of at least mild depression, the overall number of symptoms, and the PCS or MCS assessed by the SF-12 among individuals treated with DTG versus low-dose EFV [2,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost and utility were discounted at the rate of 3%. 16 In this study, $150,000 was used as the willingness-to-pay (WTP) threshold. 17 …”
Section: Methodsmentioning
confidence: 99%
“…The discount rate was 0%–6%. 16 Probabilistic sensitivity analyses were performed through Monte-Carlo simulation and were repeated 1000 times, and the results were presented in the form of cost-effectiveness acceptability curves and incremental cost-effectiveness scatter plots.…”
Section: Methodsmentioning
confidence: 99%